Ionospheric trends in Southern Hemisphere stations due to the increasing greenhouse gases concentration - Venchiarutti, José Valentín (2015)
The lower and middle atmosphere present long-term variations in temperatureand other parameters linked to anthropogenic sources, such as the increase in greenhouse gases concentration since the start of the industrial era. Some examples are the well known temperature increase in the troposphere and stratosphere cooling. Upper atmosphere parameters also present long-term variations. While in the case of the middle and lower atmosphere it is debated whether the origin of the trends is primarily anthropogenic or solar, in the upper atmosphere other sources are also able to induce long-term changes, such as long-term variations in geomagnetic activity and secular variations of the Earth?s magnetic field. In this paper, trends of the F2 layer critical frequency, foF2, measured at three Southern Hemisphere stations (Brisbane, Canberra and Christchurch) are analyzed to determine the importance of increasing greenhouse gases concentration effect. According to our results for the period covering solar cycles 18 to 21 (period 1944-1986), it is more important than natural forcings. Update estimates including solar cycle 23 are presented although the difficulty due to two of the three stations present bigdata gaps during cycle 22 and traditional ionospheric filtering is no longerentirely reliable for cycle 23. The aim of this study is to contribute both toan active area of aeronomy as is the study of trends in the upper atmosphere,and to the understanding of climate change.